Institutions count : their role and significance in Latin American development - Portes, Alejandro, 1944- (University of California Press, 2012)
What leads to national progress? The growing consensus in the social sciences is that neither capital flows, nor the savings rate, nor diffuse values are the key, but that it lies in the quality of a nation's institutions. This book is the first comparative study of how real institutions affect national development. It seeks to examine and deepen this insight through a systematic study of institutions in five Latin American countries and how they differ within and across nations. Postal systems, stock exchanges, public health services and others were included in the sample, all studied with th.